2005
DOI: 10.1152/japplphysiol.01084.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoelectrical excitation by fluid jets in monolayers of cultured cardiac myocytes

Abstract: Kong, Chae-Ryon, Nenad Bursac, and Leslie Tung. Mechanoelectrical excitation by fluid jets in monolayers of cultured cardiac myocytes. J Appl Physiol 98: 2328 -2336, 2005. First published February 24, 2005 doi:10.1152/japplphysiol.01084.2004.-Although the prevailing view of mechanoelectric feedback (MEF) in the heart is in terms of longitudinal cell stretch, other mechanical forces are considerable during the cardiac cycle, including intramyocardial pressure and shear stress. Their contribution to MEF is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Computational simulations have suggested a role for nsMSCs in heart rate acceleration and deceleration due to stretch described above, and experimental evidence in SAN tissue using GsMTx-4 is in agreement [2,72]. Computational models and experiments studies suggest a role for nsMSCs in stretch-induced ectopic ventricular contractions, repolarization shortening, and rate-dependent restitution of action potential duration [44,[73][74][75].…”
Section: Cell Scale: Myocyte Electromechanical Couplingmentioning
confidence: 65%
“…Computational simulations have suggested a role for nsMSCs in heart rate acceleration and deceleration due to stretch described above, and experimental evidence in SAN tissue using GsMTx-4 is in agreement [2,72]. Computational models and experiments studies suggest a role for nsMSCs in stretch-induced ectopic ventricular contractions, repolarization shortening, and rate-dependent restitution of action potential duration [44,[73][74][75].…”
Section: Cell Scale: Myocyte Electromechanical Couplingmentioning
confidence: 65%
“…Shear forces in the myocardium arise from blood flow and the relative movement of sheets of myocytes, causing cell deformation as the myocardial layers slide against each other with each heart beat (23,24). Although the effect of shear stress upon cardiomyocytes has not been extensively explored, it has been shown that increased shear stress stimulates intracellular calcium transients (25,26), induces an increase in the beating rate of neonatal ventricular myocytes (27), and triggers propagating action potentials (APs) in monolayers of ventricular myocytes (28). Thus far, the response to shear stress remains relatively unknown, particularly with regard to ion channel regulation.…”
mentioning
confidence: 99%
“…Next to features such as culture medium perfusion, the presence of hemoglobin via oxygen carriers in the culture medium or the acting of cyclic stretch, electrical field stimulation is the most important to mimic heart tissue. Electrical field was used for development of in vitro models of arrhythmia, investigation of cardiac phenotype or analysis of cells migration and orientation (Bian and Tung, 2006, Sathaye et al, 2006, Kong et al, 2005Xu et al, 2014, Nunes et al, 2013, Lasher et al 2012, Kujala et al 2012). Moreover, electrical stimulation can be used to enhance function of the cardiac cells and the formation of synchronously beating tissue (Radisic et al, 2004Hirt et al, 2014.…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 99%